Geospatial technologies for Chang'e-3 and Chang'e-4 lunar rover missions. Issue 1 (2nd January 2020) - Di, Kaichang; Liu, Zhaoqin; Wan, Wenhui; Peng, Man; Liu, Bin; Wang, Yexin; Gou, Sheng; Yue, Zongyu
ABSTRACT: This paper presents a brief overview of the geospatial technologies developed and applied in Chang'e-3 and Chang'e-4 lunar rover missions. Photogrammetric mapping techniques were used to produce topographic products of the landing site with meter level resolution using orbital images before landing, and to produce centimeter-resolution topographic products in near real-time after landing. Visual positioning techniques were used to determine the locations of the two landers using descent images and orbital basemaps immediately after landing. During surface operations, visual-positioning-based rover localization was performed routinely at each waypoint using Navcam images. The topographic analysis and rover localization results directly supported waypoint-to-waypoint path planning, science target selection and scientific investigations. A GIS-based digital cartography system was also developed to support rover teleoperation.